2008
DOI: 10.1001/archgenpsychiatry.2007.27
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Heritability of Cortisol Reactivity to Stress as a Function of Early Familial Adversity Among 19-Month-Old Twins

Abstract: This pattern of differing genetic and environmental contributions according to familial adversity suggests that, early in life, high familial adversity may have a programming developmental effect on cortisol reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 106 publications
4
66
1
5
Order By: Relevance
“…It has been shown that genetic factors (e.g., the serotonin transporter gene 5-HTTLPR, and FKBP5 which is associated with GR responsiveness) may in part determine who is at risk to develop psychopathology after being exposed to childhood abuse (see Caspi et al, 2003;Kendler et al, 2005;Binder et al, 2008). Interestingly, some of these same genes also appear to be associated with alterations in HPA-axis reactivity after stress exposure (Binder et al, 2008;McCormack et al, 2009; see also Ouellet-Morin et al, 2008). When investigated in combination with other risk and protective factors (i.e., social support, and exposure to adult negative and positive life events), gene  environment studies on HPA-axis reactivity might help to identify the more vulnerable vs resilient individuals in the face of early life stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that genetic factors (e.g., the serotonin transporter gene 5-HTTLPR, and FKBP5 which is associated with GR responsiveness) may in part determine who is at risk to develop psychopathology after being exposed to childhood abuse (see Caspi et al, 2003;Kendler et al, 2005;Binder et al, 2008). Interestingly, some of these same genes also appear to be associated with alterations in HPA-axis reactivity after stress exposure (Binder et al, 2008;McCormack et al, 2009; see also Ouellet-Morin et al, 2008). When investigated in combination with other risk and protective factors (i.e., social support, and exposure to adult negative and positive life events), gene  environment studies on HPA-axis reactivity might help to identify the more vulnerable vs resilient individuals in the face of early life stress.…”
Section: Discussionmentioning
confidence: 99%
“…21 Traditionally, genetic predispositions were thought to play a major role in determining stress reactivity, but more recent data suggest that previous experiences also play an important role. 22 Stress reactivity, much like brain development itself, results from a complex, dynamic interaction between genes (nature) and the environment (nurture) over time. Neural pathways activated in response to frequent environmental stimuli are strengthened over time.…”
Section: Measuring Adversity: the Physiologic Stress Responsementioning
confidence: 99%
“…Twin cohorts offer considerable potential for studying diet-genotype interactions and global impact of genomic variation in response to diet despite not being used extensively in nutrigenetics [9,28,49]. Studies include quantification of specific diet-gene interactions in identical and fraternal twins [e.g.…”
Section: Twin Studiesmentioning
confidence: 99%